Transactions on computational science XIX : special issue on computer graphics - Tan, C. J. Kenneth; Konushin, Anton; Gavrilova, Marina L. (Lecture notes in computer science, 2013)
The 19th issue of the Transactions on Computational Science journal, edited by Anton Konushin, is devoted to the topic of computer graphics. The 12 papers in the volume constitute revised and extended versions of a selection of contributions presented at GRAPHICON 2012, the 22nd International Conference on Computer Graphics and Vision, held in Moscow, Russia, in October 2012. The selected papers span the areas of scientific visualization, ray tracing, image processing, virtual reality, and stereo vision.